2022
DOI: 10.1002/hed.27172
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of prognostic nomograms in patients with ascending type of nasopharyngeal carcinoma: Retrospective study based on SEER database

Abstract: Background Nomograms specifically used to predict the prognosis of ascending type nasopharyngeal carcinoma (NPC) have not been constructed. Methods Data of ascending type (T3‐4N0‐1M0) NPC from the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and 2015 were extracted. Results Altogether 862 patients with ascending type NPC were enrolled, including 603 in training cohort and 259 in validation cohort. Age, marital status, pathology, grade, tumor size, T classification, and chemotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…In addition, lower histological grade, early SEER stage, negative node status, smaller tumor size, surgery at the primary site, and receiving chemotherapy were identified as independent favorable prognostic predictors for OS and CSS in elderly PDAC patients in the matched population. Histological grade, tumor stage, node status and tumor size are histological and biological characteristics of malignant neoplasms, which have been confirmed as prognostic features for OS in multiple malignancies, including PDAC[ 24 - 26 ]. Our results were consistent with those of previous studies[ 12 , 23 , 27 ], which have suggested that older patients are less likely than younger patients to accept or be prescribed surgical treatment that might extend their lives.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lower histological grade, early SEER stage, negative node status, smaller tumor size, surgery at the primary site, and receiving chemotherapy were identified as independent favorable prognostic predictors for OS and CSS in elderly PDAC patients in the matched population. Histological grade, tumor stage, node status and tumor size are histological and biological characteristics of malignant neoplasms, which have been confirmed as prognostic features for OS in multiple malignancies, including PDAC[ 24 - 26 ]. Our results were consistent with those of previous studies[ 12 , 23 , 27 ], which have suggested that older patients are less likely than younger patients to accept or be prescribed surgical treatment that might extend their lives.…”
Section: Discussionmentioning
confidence: 99%